Room Temperature Processed Highly Efficient Large‐Area Polymer Solar Cells Achieved with Molecular Engineering of Copolymers. Issue 21 (16th April 2019) - Rasool, Shafket; Vu, Doan Van; Song, Chang Eun; Lee, Hang Ken; Lee, Sang Kyu; Lee, Jong‐Cheol; Moon, Sang‐Jin; Shin, Won Suk
Abstract: The room temperature (RT) processability of the photoactive layers in polymer solar cells (PSCs) from halogen‐free solvent along with their highly reproducible power conversion efficiencies (PCEs) and intrinsic thickness tolerance are extremely desirable for the large‐area roll‐to‐roll (R2R) production. However, most of the photoactive materials in PSCs require elevated processing temperatures due to their strong aggregation, which are unfavorable for the industrial R2R manufacturing of PSCs. These limiting factors for the commercialization of PSCs are alleviated by synthesizing random terpolymers with components of (2‐decyltetradecyl)thiophen‐2‐yl)naphtho[1, 2‐c:5, 6‐c′]bis[1, 2, 5]thiadiazole and bithiophene substituted with methyl thiophene‐3‐carboxylate (MTC). In contrast to the temperature‐dependent PNTz4T polymer, the resulting random terpolymers (PNTz4T‐MTC) show better solubility, slightly reduced crystallinity and aggregation, and weaker intermolecular interaction, thus enabling PNTz4T‐MTC to be processed at RT from a halogen‐free solvent. Particularly, the PNTz4T‐5MTC‐based photoactive layer exhibits an excellent PCE of 9.66%, which is among the highest reported PCEs for RT and ecofriendly halogen‐free solvent processed fullerene‐based PSCs, and a thickness tolerance with a PCE exceeding 8% from 100 to 520 nm. Finally, large‐area modules fabricated with the PNTz4T and PNTz4T‐5MTC polymer have shown 4.29% and 6.61% PCE respectively, with an area as high as 54.45 cm 2 in air. Abstract : A series of room‐temperature and ecofriendly solvent processable polymers are designed and synthesized by backbone modification of the high temperature processable PNTz4T polymer. The resulting random terpolymer (PNTz4T‐5MTC)‐based solar cells show 9.66% power conversion efficiency (PCE) on a small area (0.12 cm 2 ) and an outstanding 6.61% PCE on large‐area module (54.45 cm 2 ) at room temperature processing conditions in air.